Socio-emotional skills of teachers in training and graduates of education programs - Rendón, María Alexandra (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The socio-emotional skills and teaching styles of teachers in training and graduates of the University of Antioquia Faculty of Education is a quantitative, non-experimental, cross-sectional descriptive and correlational study. The findings are in line with the aim of assessing the socio-emotional skills of such teachers in training and graduates. The sample consisted of 131 participants, among graduates and enrolled students. Two instruments were used: a scale-type questionnaire to assess socio-emotional skills and the Trait Meta-Mood Scale (TMMS 24) to measure emotional intelligence. Nineteen surveyees were found to have a medium socio-emotional skill level and 112 have a high level. Leadership is the lowest rated skill (60,7%). The highest rated skill was conflict management (85,4%), followed by integrity (84,9%) and self-assessment (84,8%). With regard to the emotional intelligence test, the lowest average score came from the emotional perception factor with 28,9 points, and the highest came from emotional regulation with 30,3 points.